Assessment of atmospheric aerosols over Varanasi: Physical, optical and chemical properties and meteorological implications. (1st November 2020) - Kumar, Pradeep; Pratap, Vineet; Kumar, Akhilesh; Choudhary, Arti; Prasad, Rajendra; Shukla, Anuradha; Singh, R.P.; Singh, Abhay Kumar
Abstract: The present paper reports the results derived from PM2.5 and PM10 concentrations during October 2016–May 2018 using MICROTOPS-II Sunphotometer and high volume samplers at Varanasi. Observed data were categorized and analyzed in order to understand the nature, source of origin and variability with seasons. Observations showed aerosol mass loading during the post-monsoon 2016 and winter 2017 as compared to the pre-monsoon 2018 values, which typically exceed national standard. The close relationships between PM2.5 and PM10 during post-monsoon (r = 0.571) and winter (r = 0.799) suggested that both type of particulates might have originated from the same source. Further, the PM2.5 /PM10 indicated that the fine particles were dominantly present during the post-monsoon and winter season where as coarse particles were found dominant in the pre-monsoon season. The measured high values of aerosol optical depth (AOD) and angstrom exponent (AE) during post-monsoon and winter attributed to the accumulation of aerosols from sources and biomass/crop residue burning in the surrounding region and low dispersal due to shallow boundary layer and lower wind velocity. In contrast during pre-monsoon months the aerosols were accumulated as a mixture of transported from deserts and other far away regions including mineral from earth crust. The effect of meteorological parameters (temperature, wind speed and relative humidity) was also studied. Temperature did not show any relation during the pre monsoon when it was quite high, whereas during the winter months it showed negative trend with concentration. Wind showed negative correlation during the whole observation period. Relative humidity showed weak positive correlation during winter months for PM2.5 and PM10 where as PM2.5 did not show any relation during pre and post monsoon. PM10 showed weak negative relation during pre monsoon months. In order to understand elemental and ionic composition Scanning electron microscope (SEM) coupled with energy dispersive X-ray microanalyzer (EDX) analysis were done which showed dominant presence of C, F, O, Si, N, Na, K, Al, Ca and S. The following trend SO4 2− > NO3 − > Na + > Ca 2+ > K + > Cl − > F − > Mg 2+ > Li + was observed from the Ion chromatograph (IC) analysis. The source for these elements may have been different industrial activities, biomass burning and vehicular emissions. The results are useful for further planning of city developments and climate studies. Highlights: AOD and AE were analyzed as obtained from ground and satellite based measurements. Chemical characteristics of particulate matters have been also analyzed during 2016–18. High aerosol mass loading was recorded during post-monsoon 2016, winter 2017 and pre-monsoon 2018. Ion Chromatography reveals SO4 2−, Cl −, K +, NO3 −, Na +, Ca 2+, Mg 2+ are the major ions present. SEM–EDX analysis shows C, F, O, Si, N, Na, K, Al, Ca and S elements were found dominant.